Virtual Learning Education about Adolescent Growth and Development - Greiny Arisani; Wahyuni, Seri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Growth and development have an important role in forming a healthy human being where a adolescent with good physical growth will have good psychomotor development as well. Usage of the distinctive features of adolescent development is the stage where adolescents experience a crisis due to physical and psychosocial changes. The growth of primary sex organs has implications for the emergence of sexual desire and attraction to the opposite sex. The growth of secondary sex characteristics such as breast protrusion in adolescent girls, testicular enlargement in adolescent boys, growth of armpit hair or pubic hair that is too late or too early often causes feelings of shame, inferiority and lack of confidence because they feel different from their peers. The implementation method is in the form of health education in the form of youth education about the growth and development of adolescents which is carried out virtually/online through the application zoom Meeting. The average result of adolescent knowledge before being given education about adolescent growth and development was at an average knowledge score of 43.3 and the average score after being given education about adolescent growth and development was a significant increase, namely knowledge score of 71. Educational activities through virtual learning Educational conducted online is an alternative to effective health education activities in increasing adolescent knowledge.